PERMAINAN TRADISIONAL DAN KONTRIBUSINYA UNTUK SIKAP HORMAT ANAK - Thomas Reno Pratama Hadi; Gregorius Ari Nugrahanta (Jurnal Education and Development, 2021)
The purpose of this research was to develop a manual for traditional games to improve the character of respect for children aged 9-12 years. This research used the ADDIE Research and Development (R&D) method which involves seven teachers from various regions for needs analysis, seven validators for expert judgment, and six children for limited manual testing. The results show that 1) traditional game manuals to development the character of respect for children aged 9-12 years were developed based on the stages of the ADDIE type, namely Analyze, Design, Develop, Implement, and Evaluate; 2) The quality of the traditional game manual received a score of 3.81 (range 1-4) and was declared "Very good" and "No revision needed" as suggestions; and 3) The application of traditional game manuals had an effect on the character of children's respect, indicated by the results of the significance test obtaining t (5) = 5.159; p = 0.004 (p < 0.05). The effect of the manual intervention was r = 0.999 which was equivalent to 99.99% belonging to the "Big Effect" category. This means, traditional game manuals could describe 99.99% of the shifts that occured in respectful character traits. The level of effectiveness was obtained based on the value of the N-Gain Score, which was 89.6465% which belonged to the type of effectiveness "High".